Rapid Influenza Antigen Test for Diagnosis of Pandemic (H1N1) 2009 - Louie, Janice K. (Centers for Disease Control and Prevention, 2010)
We compared the QuickVue Influenza test with PCR for diagnosing pandemic (H1N1) 2009 in 404 persons with influenza-like illness. Overall sensitivity, specificity, and positive and negative predictive values were 66%, 84%, 84%, and 64%, respectively. Rapid test results should be interpreted cautiously when pandemic (H1N1) 2009 virus is suspected.